Ancora sulle psicoterapie di gruppo. Un dibattito con Massimo Fagioli - Vari, Autori (Il sogno della farfalla, 2010)
Six years after the debate published in the second issue, 2003 of “Il sogno della farfalla”, the editorial board discussed once again group psychotherapy and the various aspects of a practice that distinguishes most of the therapists that make up the editorial board itself. Massimo Fagioli was asked many questions regarding problems inherent to this practice, starting from the pivotal points of his theory and the ways in which it takes place: setting, transference and interpretation . During the discussion the importance of the development of the therapist’s medical identity was highlighted given that he must offer the patient a diagnosis, treatment and a cure. Numerous reflections were made concerning the difference between the big group called the Collective Analysis conducted by Massimo Fagioli, in which treatment is linked to training and research, and the small groups conducted by the psychotherapists of the editorial board which are fundamentally characterized by treatment. Other themes treated are: group psychotherapy in the institutions; the therapist’s training, which can only be effective if he/she is able to separate this activity from his own personal therapy; the need to communicate the work carried out in the group by the therapists of the editorial board through further scientific publications.